Apoplastic barriers, aquaporin gene expression and root and cell hydraulic conductivity in phosphate‐limited sheepgrass plants. Issue 1 (17th June 2019) - Li, Lingyu; Pan, Sirui; Melzer, Rainer; Fricke, Wieland
Abstract : Mineral nutrient supply can affect the hydraulic property of roots. The aim of the present work on sheepgrass ( Leymus chinensis L.) plants was to test whether any changes in root hydraulic conductivity (Lp; exudation analyses) in response to a growth‐limiting supply of phosphate (P) are accompanied by changes in (1) cell Lp via measuring the cell pressure, (2) the aquaporin (AQP) gene expression by performing qPCR and (3) the formation of apoplastic barriers, by analyzing suberin lamella and Casparian bands via cross‐sectional analyses in roots. Plants were grown hydroponically on complete nutrient solution, containing 250 µM P, until they were 31–36 days old, and then kept for 2–3 weeks on either complete solution, or transferred on solution containing 2.5 µM (low‐P) or no added P (no‐P). Phosphate treatments caused significant decreases in root and cell‐Lp and AQP gene expression, while the formation of apoplastic barriers increased, particularly in lateral roots. Experiments using the AQP inhibitor mercury (Hg) suggested that a significant portion of radial root water uptake in sheepgrass occurs along a path involving AQPs, and that the Lp of this path is reduced under low‐ and no‐P. It is concluded that a growth‐limiting supply of phosphate causes parallel changes in (1) cell Lp and aquaporin gene expression (decrease) and (2) apoplastic barrier formation (increase), and that the two may combine to reduce root Lp. The reduction in root Lp, in turn, facilitates an increased root‐to‐shoot surface area ratio, which allocates resources to the root, sourcing the limiting nutrient.